Islamic Legal View on Crypto in Sumedang: Halal or Speculative - Faiha, Haya; Sagita, Meylani; Syahputra, Muhammad Verdy; Fitriani, Nurwulan; Nurjanah, Tiara Siti; Supriyadi, Tedi (ALSYS, 2025)
The rapid adoption of cryptocurrency as a digital asset has sparked extensive discourse within Islamic legal scholarship, particularly concerning its permissibility under Sharia law. This issue remains contentious due to the absence of authoritative legal fatwas from recognized institutions such as the Indonesian Ulema Council (MUI), compounded by concerns over gharar (excessive uncertainty), maysir (speculation), and riba (usury) inherent in cryptocurrency transactions. This study investigates the perceptions of both Islamic scholars and the local Muslim community in Sumedang, Indonesia, regarding the Sharia compliance of cryptocurrency. Employing a qualitative case study design, data were collected through participant observation, semi-structured interviews, and document analysis. The findings revealed a divergence of opinion: a majority of respondents viewed cryptocurrency as speculative and incompatible with Sharia principles, while a minority expressed conditional support, emphasizing the potential for permissibility with stringent regulatory oversight. The analysis further identified a pervasive lack of Islamic economic literacy and regulatory clarity, which exacerbates uncertainty and influences public skepticism. Younger participants, despite showing strong interest in crypto assets due to profitability and accessibility, demonstrated limited understanding of Islamic financial jurisprudence. These findings highlight the critical need for formalized guidance through fatwas, alongside robust Islamic financial education initiatives. A nuanced, Sharia-compliant framework—developed in collaboration with knowledgeable scholars—could offer pathways for integrating cryptocurrencies into the Islamic economic system in a manner that upholds doctrinal integrity.